The Impact of Profitability, Liquidity, and Company Size toward Tax Avoidance in Consumer Goods Sector Listed on the Indonesia Stock Exchange - Tarigan, Louis Yosen Primsa (Universitas Pelita Harapan, 2024)
The objective of this research is to analyze the effect of profitability (measured by return on asset, liquidity (measured by current ratio), and company size (measured by total assets) toward tax avoidance (measured by the effective tax rate) in consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the period of 2019 to 2021.The population of this research is all consumer goods sector listed on the Indonesia Stock Exchange for the period of 2019 to 2021. By using the purposive sampling method, 32 companies were selected, resulting in a total of 96 samples from three years observation. The data analysis method used descriptive statistics, classical assumption, multiple linear regression, and hypothesis test, which are processed through SPSS 26.This research finds that profitability, liquidity, and company size do not have significant effect partially on tax avoidance; while simultaneously, the tax avoidance of consumer goods sector listed on IDX from 2019-2021 is not significantly impacted by all independent variables. The adjusted R2 is 1.4%, reflecting the ability of independent variables to make impact to tax avoidance. Keywords: Profitability, Liquidity, Company Size, Tax Avoidance, Effective Tax Rate